IMPLEMENTATION OF GAMIFICATION ‘LET'S EXPLORE SCHOLARSHIP’ AS AN INNOVATIVE MEDIUM IN CLASSICAL GUIDANCE SERVICES: ACCESS TO SCHOLARSHIP INFORMATION AT SMAN 5 SERANG CITY - Cristanti, Alfina; Kusuma, Bunga Novelya; Fujiyanti, Annisa; Fadhlih, Ahdanisa; Prabowo, Arga Satrio (Universitas Dharmawangsa Medan, 2025)
This research aims to analyze the effectiveness of the implementation of the gamification